Inclusive and sustainable economic growth in the 2030 Agenda: a critical analysis from the perspective of food sovereignty and the rights of nature - Giunta, Isabella; Dávalos, Javier (Iberoamerican Journal of Development Studies, 2020)
In the article, it is discussed the objective of «Economic Growth and Decent Work» (SDG8) of the 2030 Agenda, where it is associated growth with inclusion and environmental sustainability, in its intersection with SDG 2 (eradication of hunger) and SDG 13 (climate action). This analysis is carried out from two transformative horizons of development proposed by social movements and organizations in Ecuador —food sovereignty and the rights of nature—, asking: how are inclusion and environmental sustainability conceptualized and what are their scope?; are there any official actions taken to break with discrimination, dispossession and overexploitation produced metabolically by the capitalist system? The main objective is to analyze to what extent the actions reported by Ecuador in compliance with the 2030 Agenda related to «inclusive and sustainable growth», «zero hunger», and «climate action» take distance from the logics of accumulation and extractivism and how collective action could contribute to a critical and transformative orientation of the territorialization of the SDGs.